Crosses between monokaryons of Pleurotus sapidus or Pleurotus florida show an improved biotransformation of (+)-valencene to (+)-nootkatone - Omarini, Alejandra Beatriz (2014)
Several hundred monokaryotic and new dikaryotic strains derived thereof were established from (+)-valencene tolerant Pleurotus species. When grouped according to their growth rate on agar plates and compared to the parental of Pleurotus sapidus 69, the slowly growing monokaryons converted (+)-valencene more efficiently to the grapefruit flavour compound (+)-nootkatone. The fast growing monokaryons and the slow × slow and the fast × fast dikaryotic crosses showed similar or inferior yields. Some slow × fast dikaryons, however, exceeded the biotransformation capability of the parental dikaryon significantly. The activity of the responsible enzyme, lipoxygenase, showed a weak correlation with the yields of (+)-nootkatone indicating that the determination of enzyme activity using the primary substrate linoleic acid may be misleading in predicting the biotransformation efficiency. This exploratory study indicated that a classical genetics approach resulted in altered and partly improved terpene transformation capability (plus 60%) and lipoxygenase activity of the strains.